DIGITAL LITERACY OUTLINE FOR ONLINE PUBLIC SERVICE ACCESS IN LABURINCI VILLAGE - Mayunita, Sry; Ulfa, Maria; Fida, Wa Nur; Rajab, Rajab; Mawang Sari, Putri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program (PkM) aims to enhance digital literacy in Laburinci Village to bridge the digital divide and increase participation in online public services. The program addresses the limited understanding of digital technologies, impeding access to e-government services. By providing basic digital training, the program aims to improve skills in using smartphones and computers for accessing public services such as population administration, healthcare, and online transactions. Furthermore, the initiative includes educating participants on digital security to prevent cybercrimes. The program employs a participatory approach, involving local leaders and the community, to ensure the sustainability of digital engagement. Through these efforts, Laburinci Village aims to become a model for successful digital literacy implementation, fostering inclusivity and improving public service delivery in rural areas.